"β-Cyclodextrin nano-reactor"-catalyzed synthesis of 2H-chromene-2, 3-dicarboxylates from in-situ-generated stabilized phosphorus ylides via intramolecular Wittig reaction in water. (3rd March 2016) - Ramazani, Ali; Ahmadi, Yavar; Aghahosseini, Hamideh; Joo, Sang Woo
GRAPHICAL ABSTRACT: Abstract: A convenient one-pot synthesis of chromene derivatives from the three-component reaction of triphenylphosphine and dialkyl acetylenedicarboxylate and 2-hydroxybenzaldehyde derivatives in the presence of ß-cyclodextrin as a nano-catalyst is reported. In this reaction, ß-cyclodextrin (4.5 mole%) acts as a nano-catalyst as well as nano-reactor. This methodology is of interest due to the use of water in the presence of "ß-cyclodextrin nano-reactor" as a green reaction system.